The audio-description professional: A survey about the convergence of necessary knowledge for this professional - Castadelli, Gilson Ap [UNESP]; Orlandini, Guilherme [UNESP]; Presumido Bracciali, Ligia Maria [UNESP] (My University, 2016)
A wide range of visual representations leads among the different existent medias because that contents are often prepared for people that has the vision as the first path to acquire information. It is hard to imagine how a visually impaired person can use those contents having a full satisfaction front of too many possibilities that many times does not bring the necessary communicational accessibility. This work had the goal to know the universe of acting by audio-description professionals, that transforms images at words and to know how the experience of that professional contributes on the communicational accessibility process in order to attend the visually impaired audience. The audio-descriptor has specific particulars according to his field of acting, and his acknowledgement to perform a visual translation can be enhanced based on specific techniques, mainly considering a gold rule for audio description: ‘Describes what you see’ and by using the sequence of information contained in the 3C + SV formula, representing that the audio-descriptions must be clear, concise, correct, specific and vivid. Hence, a senior look for collaborative experiences that has as elements: the communication, the coordination and cooperation among the members of a team engaged in a production of visual translation can make the difference on show paths related to the convergence of acknowledgement for those professionals. To reach this goal is a challenge for beginners at this task, but can be a pleasure source of knowledge that transforms images in texts and possibilities that feeds the imaginary of the human mind.
Keywords: Accessibility; Audio-description; Empowerment; Visual impairment; Visual translation